Seven in a row? The Tour de France and the likelihood of Lance - Kasdan, D. O. (Significance, 2013)
Lance Armstrong has confessed that all seven of his Tour de France wins were on drugs. Should we have known before? How exceptional is that record of seven Tour de France wins in a row - how likely that it could be done by a superlative sportsman unassisted by performance-enhancing drugs? In statistical terms, how much of an outlier was that seven-in-a-row streak? Should it have raised more than vague suspicions? Is it such a statistical anomaly that it can be explained only by drugs? A list of all winners since the race started in 1903 shows that Jacques Anquetil won four times in a row (1961-64) with an earlier win in 1957; Eddy Merckx also got fourin-a-row plus one (1969-72 and 1974); Bernard Hinault won five times but not very consecutively; but Armstrong`s closest rival is Miguel Indurain, who won five times in a row between 1991 and 1995. It is perhaps worth noting that had Eddy Merckx won in 1973 (he did not compete that year) he would have had six in a row, still behind Armstrong; and that Merckx, who is generally considered to be the greatest professional cyclist ever, tested positive for drugs three times.